METHODOLOGY FOR SUSTAINABILITY ANALYSIS FOR THE ENERGY SECTOR: THE CASE OF LPG AS REPLACEMENT FOR FIREWOOD IN RURAL HOUSEHOLDS IN COLOMBIA - Mora, Santiago; Mikly, Nicole; Guarin, Viviana; Guarin, Juan; Silveira, Belen; Mora, Cesar; Bermudez, Mauricio (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2023)
In this paper we provided a sustainability analysis for the LPG energy sector in Colombia using different methodologies: analysis of primary and secondary sources of normative documents; programmatic and regulatory framework of LPG; a study on the current tax burden of fuel gas subsidies; scenarios for the expansion of LPG subsidies; a socio-environmental sensitivity analysis; identification of relevant territorial factors to make prioritization recommendations in the replacement of firewood by LPG in specific areas; LPG emissions estimations as a strategy for replacing firewood in rural homes and the analysis of the economic sustainability of the business using different indicators. The research begins with a brief introduction which describe and highlights the importance of analyzing studies of natural gas and LPG in Colombia. The first section briefly exposes the theoretical and conceptual framework that supports the research. The second section presents the methodology used for each of the analysis topics. The third section shows some of the results achieved during the investigation and the main conclusions. Finally, we provide a series of reflections and insights for sustainability research where the dialogue of knowledge and multidisciplinary is encouraged.